Application of applied statistical methods in the study of the labor market of IT-specialist - V. A. Livinskaya; M. A. Shaluchova (Системный анализ и прикладная информатика, 2022)
The methods of applied statistics are reliable mathematical tool for processing and analyzing collected statistical data. As the number and variety of devices allowing to accumulate a variety of data types increase and the spheres of human activity in which information technology is used expand, the need for modern statistical data processing tools grows.The article describes methods of applied statistics used to study the labor market of IT-industry professionals, using freely distributed tools for data analysis, one of which is a programming language for statistical data processing R.